Pengaruh Penggunaan Asam Klorida terhadap Rendemen, Kadar Air, dan Kadar Abu Gelatin Ceker Itik (Anas platyrhynchos Javanica) - Hana Aulia Andiati; Wendry Setiyadi Putranto; Jajang Gumilar (Jurnal Teknologi Hasil Peternakan, 2022)
Gelatine is a product produced from collagen hydrolysis.  Solvents that can be use in the manufacture of gelatin are acidic and basic solutions.  The acid used in this experiment is hydrochloric acid (HCl). The quality factor of gelatine can be determined from the amount of yield, moisture content, and ash content. The quality of gelatine also depends on the concentration of hydrochloric acid solution.  This experiment aims to determine the effect of HCl concentration on yield, moisture content, and ash content of gelatine from duck feet, to find the concentration of HCl that can produce the best quality of gelatine from duck feet, and to find the form of tendency between treatments of HCl concentration on yield, moisture content and ash content of gelatine from duck feet. The experiment was conducted experimentally using Completely Randomized Design (CRD).  The treatments used were HCl concentration P1 (4%), P2 (6%), and P3 (8%), with six times repetation so that there were 18 experimental units.  The results showed that the use of hydrochloric acid 6% can gave the best quality of gelatine from duck feet with 8,04% yield, 5,99% moisture content, and 3,98% ash content.